Subtract the sum of (4y2 - 6y) and (-2y2 + 3y - 3) from the sum of (5y + 7) and (3y2 - 9y + 2)
Attachments:
![](https://hi-static.z-dn.net/files/d26/96223a644997169a4c95550fc85b85e3.png)
Answers
Answered by
4
5y+7+3y2-9y+2
=3y2-4y+9
4y2-6y-2y2+3y-3
=2y2-3y-3
3y2-4y+9-2y2+3y+3
=3y2-4y+9
4y2-6y-2y2+3y-3
=2y2-3y-3
3y2-4y+9-2y2+3y+3
Answered by
1
The answer is in the image attached..hope it's helpful
Attachments:
![](https://hi-static.z-dn.net/files/dd4/337d07d95069e470282b96d6d2177407.jpg)
Similar questions